2020
DOI: 10.1038/s41598-020-70429-9
|View full text |Cite
|
Sign up to set email alerts
|

Neutron activation of gadolinium for ion therapy: a Monte Carlo study of charged particle beams

Abstract: this study investigates the photon production from thermal neutron capture in a gadolinium (Gd) infused tumor as a result of secondary neutrons from particle therapy. Gadolinium contrast agents used in MRi are distributed within the tumor volume and can act as neutron capture agents. As a result of particle therapy, secondary neutrons are produced and absorbed by Gd in the tumor providing potential enhanced localized dose in addition to a signature photon spectrum that can be used to produce an image of the Gd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Using the microdosimetric strand break results determined from within this study, a total of effectively 1.8 × 10 8 SSBs and 6.8 × 10 6 DSBs for 1 Gy of proton dose can be calculated. From results produced in another MC simulation study, a 5–10 cm SOBP beam of protons, carbon ions, and helium ions incident on an 8 cm 3 volume of 3000 PPM Gd resulted in 2.1 × 10 6 , 1.1 × 10 6 , and 3.7 × 10 6 neutron captures per Gy of absolute dose 20 . Therefore, the total strand breaks can be calculated as: 8.2 × 10 7 SSBs, 3.1 × 10 6 DSBs for protons, 4.3 × 10 7 SSBs, 1.6 × 10 6 DSBs for carbon ions and 1.5 × 10 8 SSBs, 5.5 × 10 6 DSBs for helium ions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the microdosimetric strand break results determined from within this study, a total of effectively 1.8 × 10 8 SSBs and 6.8 × 10 6 DSBs for 1 Gy of proton dose can be calculated. From results produced in another MC simulation study, a 5–10 cm SOBP beam of protons, carbon ions, and helium ions incident on an 8 cm 3 volume of 3000 PPM Gd resulted in 2.1 × 10 6 , 1.1 × 10 6 , and 3.7 × 10 6 neutron captures per Gy of absolute dose 20 . Therefore, the total strand breaks can be calculated as: 8.2 × 10 7 SSBs, 3.1 × 10 6 DSBs for protons, 4.3 × 10 7 SSBs, 1.6 × 10 6 DSBs for carbon ions and 1.5 × 10 8 SSBs, 5.5 × 10 6 DSBs for helium ions.…”
Section: Discussionmentioning
confidence: 99%
“…The results for the three highest thermal neutron production values were from helium ions, antiprotons, and negative pions with values of 1.3 × 10 6 , 1.4 × 10 7 , and 2.9 × 10 7 (cm −2 ) per Gy of dose. A value of 7.4 × 10 5 (cm −2 ) thermal neutrons per Gy of proton dose was determined within this study 20 . Several studies have measured the thermal neutron fluence (cm −2 ) production per Gy of proton dose at various distances away from the isocenter.…”
Section: Introductionmentioning
confidence: 98%
“…The BSA consists of a magnesium fluoride moderator, a composite reflector (graphite in the front hemisphere and lead in the back), an absorber, and a filter. Monte Carlo radiation transport tools are used to design and optimize a neutron source [24][25][26][27][28], X-ray-radian-and gamma-radianbased systems [29,30]. Numerical simulations of neutron and γ-radiation transport showed that at a proton beam energy of 2.3 MeV, the BSA makes it possible to produce a neutron beam with parameters well-matching the BNCT requirements [31,32].…”
Section: Beam-shaping Assemblymentioning
confidence: 99%
“…Additionally, 10 B's daughter products are more massive and deposit their energy over a shorter range than those of 6 Li: Natural gadolinium, which consists of seven stable isotopes, has a total thermal neutron cross-section of 48,800 barns. Two isotopes that have high thermal neutron capture cross-sections and a relatively high natural abundance are 155 Gd (60,900 b, 14.8% abundance) and 157 Gd (254,000 b, 15.7% abundance) [40]. As shown in Equations ( 4) and ( 5), gadolinium neutron absorption reactions produce prompt γ-rays and internal conversion electrons (IC e− ), which also produce secondary characteristic X-rays and Auger electrons, including Coster-Kronig electrons.…”
Section: Theory Of Boron-based Scintillator Screensmentioning
confidence: 99%
“…Thermal neutron capture by 157 Gd, for example, releases an average of 3.288 photons including prompt and secondary γ-rays and X-rays with energies ranging from 10s of eV up to several MeV and a mean energy of 2.394 MeV [42,43]. This same reaction also releases IC e− with energies ranging from 29 keV to 6.9 MeV, with the most intense discrete IC e− emissions of 29 and 71 keV [40,43,44]. The range of a 71 keV IC e− in gadolinium is approximately 20 µm [45].…”
Section: Theory Of Boron-based Scintillator Screensmentioning
confidence: 99%